Efetivação das sentenças estrangeiras sobre o estado das pessoas no Brasil: por uma mudança de paradigma à luz da globalização econômica - Azevedo, Ana Paula Schoriza Bueno de (2011)
The economic globalization brought as a result the major interdependency between the countries. This also causes the increase of litigations involving more than one legal system. In fact, more and more, the Judiciary has to effectuate foreign judgments, so it becomes necessary the international judicial cooperation. The foreign judgments can‟t be confused with the international judgments, which don‟t need recognition and are rendered by the international courts or international organizations. The foreign judgments from any nature need to be recognized by the Superior Court of Justice (Superior Tribunal de Justiça), which will analyze the presence of legal requisites. However, this affirmation is refused by doctrine and jurisprudence in cases of foreign judgments involving the person‟s status. In spite of the existence of some right points of view of the major doctrine, the problem must be reexamined considering the presence of interest, because there is no regular application of the action of recognition when it‟s not necessary to modify the status in Brazil. Also it must be emphasized that the foreign judgments or any other decisions regarding the Law 11.441/2007. Notwithstanding, it‟s necessary to regulate the recognition of foreign judgments, specially regarding the person‟s status, in order that is possible to satisfy the cooperative and globalized society